Leonurine negatively modulates T cells activity by suppressing recombination activation gene protein 2 in pulmonary fibrosis. (2nd August 2021) - Zhu, Yongping; Lin, Bixia; Ding, Fadian; Ma, Fenfen; Zhou, Xiaohui; Zong, Haiyang; Feng, Gao; Chen, Qingquan; Chen, Gongping; Lv, Xiaoting
Introduction: The key transformed T cell transcription factor recombination activation gene protein 2 (RAG2) is regulated during inflammation to allow for the acquisition of effector T cells functions. The present study was designed to investigate whether stress signals elicited by leonurine (LEO) could lead to the degradation of RAG2 through v-akt murine thymoma viral oncogene homolog (AKT) signaling in lung fibrosis. Methods: A total of 120 female mice were randomly divided into five groups (Group I–V): Normal group, bleomycin (BLM), BLM+LEO 50 mg/kg/d, BLM+LEO 100 mg/kg/d, and BLM+LEO 50 mg/kg/d+LY294002. Hematoxylin-eosin, Masson's, and terminal deoxynucleotidyl transferase dUTP nick-end labeling staining were performed to observe the pathomorphological changes. The expression of CD3 +, TGF-β, RAG2, and Bcl proteins was examined by immunodetection, while that of E-cadherin (ECAD), AKT, TGF-β1, alpha-actin-2, Bax, and RAG2 was detected by Western blot analysis. Results: The level of T lymphocytes was reduced sharply in LEO-treated mice as compared to the other groups. The AKT signal was greatly inhibited in the BLM group and activated with LEO treatment on day 14. In addition, RAG2 was attenuated by LEO on day 14 and day 28. LY294002 could reverse the expression of AKT and RAG2 on day 28. Remarkably, the low dose of LEO has a greater protective efficacy as compared to the high-dose LEO group in terms of pulmonary fibrosis, T cell inactivation, and apoptosis in alveolar cells. Conclusion: The results of the present study suggested that LEO has a protective effect on lung fibrosis with possible mechanisms of attenuating apoptosis and inflammation via the upregulation of the AKT signal in transformed T cells by suppressing the expression and activity of RAG2.